Isolasi dan Identifikasi Bakteri Pelarut Fosfat dari Tanah Gambut - Larasati, Ella Dewani; Rukmi, MG Isworo; Kusdiyantini, Endang; Ginting, R Cinta Badia (Bioma : Berkala Ilmiah Biologi, 2018)
Phosphate (P) are macronutrients that necessary for growth and development of plants, But the availability of phosphate dissolved in the ground are very limited because trend is bound to minerals ground form phosphate complexs. One of the alternative to improve the efficiency of phosphate is by utilize phosphate solubilizing bacteria. Phosphate solubilizing bacteria is bacteria capable of dissolving phosphate that is not available become available, so that it can be absorbed by plants. Peat soils can be used as a source of phosphate solubilizing bacteria because , peat soils formed from litter and organic matter so, many microorganisms which live in peat soils one of them is a phosphate solubilizing bacteria. The aim of this research is to isolat, identify bacteria to species level using Biolog system GenIII Mircoplate, and test the ability of phosphate dissolution. The isolation is done with the methods spread plate in a media pikovkaya solid and testing the ability to isolat qualitatively glimpsed clear zone around colonies, measuring phosphate solubilizing index. testing the ability isolats quantitatively by measuring solubility phosphate using spektrofotometer, and identification isolats using Biolog System. Eighteen isolates phosphate solubilizing bacteria successfully obtained from of peat soils, two isolates of them potential in solubilizing phosphate, According to Biolog system the second isolates identified as Pseudomonas tolaasii (isolate PG2T.5) and a Bacillus pumilus (isolate PG3TT.2), each is about phosphate dissolved successive of 24,81 mg/L and 22,62 mg/LÂ Key words: Peat Soil, Isolation, Phosphate SolubilizingÂ  Bacteria, Biolog System Identification